10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Goat mastitis is an economically important disease that reduces milk yield and quality while also posing a public health risk due to antimicrobial-resistant pathogens. OBJECTIVES: This study aimed to evaluate mastitis diagnostic techniques, isolate Staphylococcus aureus, detect methicillin-resistant S. aureus (MRSA) and assess the antibacterial potential of 6-gingerol alone and in combination with antibiotics. METHODS: A total of 2000 aseptically collected milk samples were obtained from lactating goats presented at the Civil Veterinary Hospital, Chargano Chowk and the Veterinary Teaching Hospital, The University of Agriculture Peshawar, Pakistan. Samples were screened using the Surf Field Mastitis Test and confirmed by the California Mastitis Test (CMT). Positive samples were cultured on selective media, and S. aureus was identified through Gram staining, catalase and coagulase tests. MRSA detection was performed using PCR amplification of the mecA gene. Antimicrobial susceptibility was assessed using the Kirby-Bauer disc diffusion method according to CLSI guidelines. The antibacterial activity of standard and extracted 6-gingerol, selected antibiotics and enrofloxacin plus 6-gingerol combination therapy was evaluated using inhibition zone diameter and minimum inhibitory concentration (MIC) assays. RESULTS: The Surf Field Mastitis Test showed high diagnostic performance with excellent sensitivity, moderate specificity and substantial agreement with the CMT. S. aureus isolates exhibited varying resistance patterns, with confirmed presence of MRSA strains via mecA gene detection. Among treatments, enrofloxacin demonstrated the highest individual antibacterial activity, while extracted 6-gingerol showed moderate inhibitory effects. The combination of enrofloxacin with 6-gingerol exhibited the strongest antibacterial activity, surpassing all single-agent treatments. MIC analysis confirmed a concentration-dependent inhibitory effect of 6-gingerol against S. aureus. Correlation analysis showed a strong negative relationship between increasing compound concentration and bacterial growth, while combination therapy significantly enhanced antimicrobial efficacy. CONCLUSION: These findings demonstrate that rapid field diagnostics are effective for mastitis screening and suggest that 6-gingerol, particularly in combination with enrofloxacin, may serve as a promising adjunct antimicrobial strategy for controlling resistant S. aureus in goat mastitis.